Докажите, что значение выражения не зависит от переменной x: 1) (x-0,7)(0,7+x)+5-x^2 2)(5-0,9x)(0,9x+5)-10+0,81x^2 3)(x-0,2)*(0,2+x)+(4-x)(4+x) 4)(0,6-x)(x+0,-x)(x+2)

ЮлияYli ЮлияYli    2   10.07.2019 19:30    2

Ответы
Omniscient1www Omniscient1www  17.09.2020 14:26
1) = (x-0,7)(x+0,7)+5-x^2=x^2-0,49+5-x^2 =4,51     
2)=(5-0,9x)(5+0,9x)-10+0,81x^2=25-0,81x^2-10+0,81x^2=15
3)=(x-0,2)(x+0,2)+(4-x)(4+x)=x^2-0,04+16-x^2=15,96
4)=(0,6-x)(0,6+x)-(2-x)(2+x)=0,36-x^2-4+x^2=-3,64
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра